Investigating Transcriptional Age Acceleration in Inflammatory Skin Diseases - Richie Jeremian; Melissa Galati; Rayyan Fotovati; Kaiyang Li; Carolyn Jack; David O. Croitoru; Stephan Caucheteux; Philippe Lefrançois; Vincent Piguet (JID Innovations)
Epigenetic age acceleration has previously been observed in inflammatory skin disease; however, less is known regarding recently described age-related gene expression patterns (“transcriptional clocks”). We investigated the role of transcriptional clocks in patients with hidradenitis suppurativa (n = 37), those with atopic dermatitis (n = 27), those with plaque psoriasis (n = 28), and healthy subjects (n = 38) using 7 clock algorithms, to improve the understanding of underlying pathophysiology and disease trajectory. Five of 7 transcriptional clocks demonstrated moderate-to-strong accuracy in predicting age across groups (patients with atopic dermatitis: ρ = 0.40–0.86, those with hidradenitis suppurativa: ρ = 0.46–0.74, those with plaque psoriasis: ρ = 0.50–0.80, healthy subjects: ρ = 0.32–0.60; P < .05). Age acceleration was observed in lesional versus healthy (patients with atopic dermatitis: +3.9∼9.8y, t = 2.8∼5.9; those with hidradenitis suppurativa: +5.0∼6.1y, t = 2.5∼4.1; those with plaque psoriasis: +6.5∼12.5y, t = 5.1∼8.0; P < .05) and in lesional versus nonlesional skin in all diseases and less frequently observed in nonlesional versus healthy skin. In atopic dermatitis, loss-of-function sequence variants in the FLG gene were associated with transcriptional age acceleration, including FLGR244X/2282del4 dual carrier status (t = 2.3, P < .05) and FLGR501X carrier status (t = 2.6, P < .05). Pathway enrichment analyses revealed that clock genes are enriched in signatures related to aging, inflammation, and metabolism. Our study provides evidence for transcriptional age acceleration in inflammatory skin disease and sets a foundation for further investigation into the role of age-related transcriptional changes in the pathophysiology of these diseases.